Man, moment, machine. The red baron & the wings of death [videorecording (DVD)] - Ellis, Hunter, 1968- (A & E Television Networks : Distributed by New Video, 2009)
Provides a concise biographical recounting of the military life of Manfred Richthofen, commonly referred to as the Red Baron. Examines the aircraft and military tactics employed by both English and German pilots during the aerial dogfights of WWI. A number of the baron's most daring and harrowing missions, including the period known as Bloody April, are recreated using actors, visual effects and interviews with historical scholars.